Bibliometric Analysis of Sustainable Tourism Research in Bali (2020-2025) - Ningsih, Sabda; Fachrurreza, Ahmad Mujaddid (Universitas Muhammadiyah Jember, 2025)
This study aimed to extend the previous research conducted by Yospetch and Nimsai, as well as Kawuryan, concerning the global prominence of sustainable tourism research in Asia and Indonesia. The novelty of this study lay in its specific focus on sustainable tourism in Bali, a region with a longstanding history in tourism management. A relational bibliometric analysis was employed to provide a comprehensive overview of the relationships between metadata and analytical units, using tools such as PoP, Mendeley Desktop, and VOSviewer. From an analysis of 16 Scopus-indexed academic publications, three key findings were identified. First, a new research theme emerged between 2020 and 2025, namely the evaluation of government policy frameworks in relation to sustainable tourism. Second, the limited global visibility of research on sustainable tourism in Bali was attributed to the lack of international collaboration and the restricted diversity of keywords employed. Third, a discernible shift was observed in the dominant research themes between the periods 2010-2019 and 2020-2025. This thematic transition indicated potential avenues for future scholarly inquiry that could offer greater significance and impact within the international academic community.